DRINKING AND CLEAN WATER QUALITY, SANITATION AND WATER SERVICE LEVELS AT DAYAH INTI DARUL AITAMI, WEST ACEH - Ashari, Teuku Muhammad; Rohendi, Aulia; Dipa, Syahrul Ridha; Effendi, Rijal; Tanjung, Aris Muda (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2025)
This study assesses drinking-water and clean-water quality and sanitation conditions at Dayah Inti Darul Aitami, West Aceh, to support healthier boarding-school environments. A mixed-methods case study was conducted, combining laboratory water-quality testing with field observation/interviews and an exploratory questionnaire of 10 santri. Laboratory results show that Reverse Osmosis (RO)-treated drinking water met key benchmark parameters (turbidity 0.45 NTU, TDS 14 mg/L, pH 6.68) and showed “Not Detected” results in the H₂S pathogen indicator test at both 1×24 h and 3×24 h incubation. In contrast, borehole-derived clean water exceeded the TDS benchmark (412 mg/L) and showed “Detected” results for the H₂S pathogen indicator test at both incubation periods. Questionnaire responses were consistent with these patterns: 8/10 respondents rated drinking-water quality as satisfactory, whereas only 5/10 rated clean-water quality as acceptable, citing odor and discoloration. Sanitation challenges were also reported, particularly inadequate toilet cleanliness (3/10 respondents) and suboptimal solid-waste management (4/10 respondents). Overall, while access to water sources is adequate, improvements are needed in clean-water treatment and source protection, routine monitoring, and sanitation management to reduce health risks and strengthen Eco-Dayah implementation.